2000
DOI: 10.14341/probl11833
|View full text |Cite
|
Sign up to set email alerts
|

Early and long-term neuroendocrine effects of prenatal stress in male and female rats

Abstract: The effect of maternal stress or so-called prenatal stress (PS) on the neuroendocrine regulation of reproduction and stress reactivity of the progeny was studied. Prenatal stress prevented the formation of sex dimorphism of catecholamine content and aromatase and androgen 5a-reductase activities in the preoptic region of the brain and mediobasal hypothalamus of 10-day-old rats. Leveling of sex-specific differences in the size of the neurocyte nuclei in the suprachiasmatic nucleus was the morphological equivale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…The prenatal stress acts through increased glucocorticoid level and injured glutamatergic neurons to: induce morphological alterations in the hippocampus, cortex, and the raphe nuclei (Hayashi et al, 1998;Weinstock, 2001;Butkevich et al, 2005b); disrupt the balance in hormonal and neurotransmitter systems (the monoaminergic, glutamatergic, GABA-ergic, HPA); and impair receptor function, and regulation of feed-back systems (Takahashi et al, 1992;Slotkin et al, 1996;Hayashi et al, 1998;Reznikov et al, 2001;Huizink et al, 2004;Ordyan and Pivina, 2005;Weinstock, 2006). The structural and functional alterations induced by prenatal stress in the central nervous system can change the equilibrium between concurrent inhibitory and excitatory processes in it and change mechanisms underlying activation and modulation of the biphasic behavioral response to formalin injection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The prenatal stress acts through increased glucocorticoid level and injured glutamatergic neurons to: induce morphological alterations in the hippocampus, cortex, and the raphe nuclei (Hayashi et al, 1998;Weinstock, 2001;Butkevich et al, 2005b); disrupt the balance in hormonal and neurotransmitter systems (the monoaminergic, glutamatergic, GABA-ergic, HPA); and impair receptor function, and regulation of feed-back systems (Takahashi et al, 1992;Slotkin et al, 1996;Hayashi et al, 1998;Reznikov et al, 2001;Huizink et al, 2004;Ordyan and Pivina, 2005;Weinstock, 2006). The structural and functional alterations induced by prenatal stress in the central nervous system can change the equilibrium between concurrent inhibitory and excitatory processes in it and change mechanisms underlying activation and modulation of the biphasic behavioral response to formalin injection.…”
Section: Discussionmentioning
confidence: 99%
“…The structural and functional alterations induced by prenatal stress in the central nervous system can change the equilibrium between concurrent inhibitory and excitatory processes in it and change mechanisms underlying activation and modulation of the biphasic behavioral response to formalin injection. Stress during the last week of pregnancy inhibits secretion of testosterone of male fetuses, and alters the process of brain sex differentiation (Stahl et al, 1978;Ward and Weisz, 1984;Murase, 1994;Reznikov et al, 2001;Ordyan and Pivina, 2005) including that of neurotransmitter systems involved in different kinds of adaptive behavior with the male being more sensitive to reductions in the fetal testosterone surge than the female (Ward et al, 2003). Prenatal stress decreases the function of adrenal glands and testes and the decreased testosterone level persists in infant rats (Stahl et al, 1978;Ward and Weisz, 1984;Murase, 1994;Reznikov et al, 2001;Ordyan and Pivina, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary studies from our laboratory (Barros et al, 2002) showed that DA receptor overexpression seen in prenatally adult rat brains was not observed before puberty, suggesting that an early modification of neuronal reactivity to hormones and neurotransmitters may modify the normal modulation by sex steroids during puberty. Therefore, the long‐term effects of prenatal stress may result from disrupting the hormone‐neurotransmitter imprinting of the neuroendocrine system (Reznikov et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The developing central nervous system (CNS) is particularly vulnerable during phases of cellular replication, differentiation, migration, axonal outgrowth, and synaptogenesis (Johnston, 1995). Prenatal stress (PNS) is shown to cause significant structural, endocrinological, neurochemical, and behavioral changes in the brain of offspring (Hayashi et al, 1998; Poland et al, 1999; Lemaire et al, 2000; Reznikov et al, 2001).…”
mentioning
confidence: 99%